Rail cleaning process and its influence on locomotive performance - Spiryagin, M.; Wolfs, Peter; Wu, Q.; Cole, C.; Alahakoon, S.; Sun, Y.; McSweeney, T.; Spiryagin, V. (2017)
© Copyright 2017 ASME. The traction performance of a locomotive under real operational conditions is strongly dependent on friction conditions present at the wheel-rail interface. The tribology of the contact process changes during the locomotive running process and the conditions are not ideal due to the presence of a third body layer between wheels and rails. This leads to the complexities of the non-linear wheel-rail contact. To describe this system correctly, the real working conditions need to be known. The exact conditions are both complex and vary with location because of the potential presence of additional contamination material. The realization of high adhesion under traction or braking assumes that a locomotive produces a high slip that removes some of the third body material in the contact and this effect leads to an increase in values of friction coefficient from the leading to each subsequent following wheel on each side of the bogie. The resulting friction change can improve the tractive effort of a locomotive that is a key issue for railway operations. In this paper, the change of friction coefficients under traction are investigated by means of engineering analysis and some assumptions have been stated to generate input parameters for wheel-rail contact modelling in order to understand the influence of this rail cleaning process on locomotive dynamics. The assumptions made allow adopting a progressive increase of friction coefficient under an analytical assumption for each wheel. The multibody model of a high adhesion locomotive that includes a traction system has been developed in a specialized multibody software. The results obtained show the changes in dynamic behavior of a locomotive and indicate the influence on traction performance.